A method to benchmark the balance resilience of robots - Monteleone, Simone; Negrello, Francesca; Grioli, Giorgio; Catalano, Manuel G.; Bicchi, Antonio; Garabini, Manolo (Frontiers in Robotics and AI, 2023)
Robots in real unstructured scenarios must withstand collisions with the environment, other robots, or humans. Accordingly, recent research has focused on the design of robust and resilient systems. In this work, we present a framework for quantitatively assessing the resilience of self-stabilizing robotic systems subjected to external perturbations. Our proposed framework consists of a set of Performance Indicators (PIs), experimental protocols for the reliable and repeatable measurement of the PIs, and a testbed to execute the protocols. To ensure replicability, we provide the design of the structure and framework as open-source materials so that it is possible for other institutions to build their system. As an example of the application of our method, we report a set of experimental tests on a two-wheeled humanoid robot, with an experimental campaign of more than 1100 tests.